Visualisasi QS. Yusuf ayat 28 di Media Sosial: Dari Nalar Tekstualitas ke Nalar Patriarkis - Fathassururi, Fathassururi; Miski, Miski (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2025)
The memes of Qur'anic verse Yusuf 28 on social media present women as objects of visualization. As a meme, the visualization of this verse cannot be separated from deliberately constructed understandings. Therefore, this article aims to answer the question: 1) Does the understanding visualized in the memes represent the meaning of the Qur'anic verse Yusuf 28?. 2) How does this imply the existence of women? The article is a library study with a content analysis approach to the visualization of Yusuf 28 in various memes on social media. The data is collected using documentation techniques by searching social media platforms such as Instagram, Facebook, X, Telegram, Pinterest, and TikTok. The search was based on several keywords, specifically “tipu daya wanita”, “wanita tipu daya”, “tipu daya”, “tipu daya perempuan”, and the hashtag #tipudayawanita. Data was analyzed based on content (text), patterns, and the style emphasized. The study found that the understanding of Qur'anic verse Yusuf 28, regarding women as a “fitnah,” is often visualized in various memes on social media in a literal and textual manner. Furthermore, these findings imply the existence of gender inequality, marginalization, subordination, and stereotypes toward women. The reality essentially does not reflect the principles of equality and humanity that are central to the Quran's core values. These findings further strengthen the argument that the visualization of Qur'anic verses on social media regarding women tends to be biased and textual. Therefore, this article's findings can provide academic literature for governments, religious leaders, and gender activists in designing more equitable and gender-sensitive narratives and content for disseminating religious messages on social media.